Good response with durvalumab after chemoradiotherapy for epidermal growth factor receptor exon 20 insertion adenocarcinoma: A case report - Matsuura, Shun (Respir Med Case Rep, 2020)
Epidermal growth factor receptor (EGFR) exon 20 insertion is not associated with sensitivity to EGFR tyrosine kinase inhibitors and chemotherapy. Here, we report the case of a 41-year-old man who presented a right lower lobe nodule and mediastinal lymph node enlargement diagnosed as EGFR exon 20 insertion adenocarcinoma with high-expression programmed cell death ligand 1 (PD-L1). He showed stable disease to chemoradiation treatment at the primary tumor site. However, durvalumab treatment has good response. Non-small cell lung cancer with EGFR exon 20 insertion and high PD-L1 expression may be treated with immunotherapy exposure.